Needs for improvement in patient safety, perceived by pediatric intensive care professionals - Mirelys Sarduy Lugo; Yuliett Mora Pérez; Magny Martín Hernández; Anabel Sarduy Lugo; Yuleidy Fernández Rodríguez; Niurka de la Torre Cuellar (Edumecentro)
Background: improvement in patient safety is an essential element to improve the safety culture and quality of care in pediatric intensive care units. Objective: to analyze the perception that professionals linked to a pediatric intensive care unit have about the need to improve patient safety. Methods: a descriptive research with a qualitative phenomenological approach was carried out at “José Luis Miranda” Provincial Pediatric University Hospital of Villa Clara, from December 2022 to March 2023. Theoretical methods were used: analysis-synthesis, inductive-deductive, historical-logical and abstract-concrete; Empirical ones: the participatory technique of discussion groups. The data were organized by information analogy and analyzed qualitatively, for which content analysis was used. Results: the perception of professionals linked to the pediatric intensive care unit regarding training and improvement in patient safety was insufficient in terms of knowledge, improvement, prevention and management of adverse events. Conclusions: once analyzed the perception of professionals about the need to improve patient safety, it was found that it is insufficient, which influences the achievement of current safety standards in the occurrence of adverse events.